The data quality paradox. Issue 6 (June 2015) - Huard, Boris
Abstract : After its people, data is arguably an organisation's most valuable asset. According to recent figures by the Networked Systems and Services department at SINTEF, some 90% of all the data in the world has been created in the past two years. That shouldn't be too much of a surprise to us given the data-driven world we now live in; but what is promising is that companies are increasingly switching on to its strategic and commercial value. The challenge is how do we extract value from this data in a way that empowers people and organisations alike?